The Penitential Language of the Congregation of Artisans in the Neapolitan Pastoral Care of Francesco De Geronimo - Rubini, Pasquale (Confraternitas, 2020)
Between the end of the seventeenth century and the beginning of the eighteenth, the Congregation of Artisans in Naples, spiritually led by the Jesuit Fr. Francesco De Geronimo, expressed its participation in the sufferings of Christ with a public procession that included elements of corporal penance. The ritual, meant to atone for one’s own sins and those of others, also served to generate community involvement. This article examines the penitential practices of the Congregation of Artisans by contextualizing them in the missionary work of the Society of Jesus and its mission in “the internal Indies.”